Reformulation of the Legal Politics of the Parliamentary Threshold in the Design of the 2029 General Election Following Constitutional Court Decision No. 116/PUU-XXI/2023 - Barqi, Suha Yusbairoh; Yusdiyanto; Fathoni (As-Siyasi: Journal of Constitutional Law, 2026)
Indonesia's parliamentary threshold has been progressively increased over successive general elections. However, its determination has lacked objective, proportionate, and rational parameters, creating legal uncertainty and reducing political representation by excluding valid votes from parliamentary seat allocation. Constitutional Court Decision No. 116/PUU-XXI/2023 marks a constitutional turning point by requiring the legislature to reformulate the parliamentary threshold before the 2029 General Election using a constitutionally justifiable methodology. This study examines the legal politics of parliamentary threshold regulation following Constitutional Court Decision No. 116/PUU-XXI/2023 and proposes an appropriate regulatory model for the 2029 General Election. The research employs normative legal research using statutory, conceptual, case, and comparative approaches, analysed qualitatively through the theories of legal politics and democracy. The findings demonstrate that the Court's decision has transformed the concept of open legal policy from broad legislative discretion into a legal policy constrained by constitutional parameters. Comparative experience from Germany further indicates that a parliamentary threshold remains constitutionally justifiable when designed in accordance with the principles of proportionality, the protection of political representation, and empirically grounded criteria. Accordingly, this study proposes a reformulation model based on empirical and constitutional parameters by integrating the Effective Number of Parliamentary Parties (ENPP), the Gallagher Index, and wasted votes as the principal indicators for determining the parliamentary threshold. It recommends that these parameters serve as the normative basis for amending Indonesia's General Election Law before the 2029 General Election.